Volvopluteus striatellus (Pluteaceae, Agaricales), a novel species from North China - Li, Jia-He; Fu, Hao-Yu; Fan, Li (Phytotaxa, 2025)
A new fungal species, Volvopluteus striatellus, was discovered in Shanxi Province, China. Morphologically, it is characterized by a pale grey to white and striated pileus, ellipsoid to oblong basidiospores, and the absence of caulocystidia. Phylogenetic analysis based on ITS and nrLSU confirmed the taxonomic status of the new species. A description, illustrations, and phylogenetic analysis results are provided.